Review of gesture recognition for virtual automotive training applications - Zamalik, Sarah N.; Abu Bakar, Juliana Aida; Yaakub, Abdul Razak (2016)
In a virtual system, gesture is considered as a natural way for communication between human and computers.Gesture recognition is the process of recognizing and interpreting a stream of continuous sequential gesture from a given set of input data.The main goal of gesture recognition is to create a system which can recognize specific human gestures and use them to convey information or to control a device and/or application.The objective of this paper is to review gesture-based recognition methods and its applications as an approach to improve user interaction particularly for virtual automotive training.Review of applications and techniques of gesture recognition system will be provided with emphasis on hand gesture expressions.The major techniques include HMMs, ANN, and fuzzy clustering will be reviewed and analyzed.